Sociodemographics, Knowledge, Attitudes, and COVID-19 Prevention Measures in Indonesia - Sulistyawati , Sulistyawati; Haifa, Adinda (Jurnal Kesehatan Masyarakat, 2025)
The COVID-19 pandemic provides many lessons for all countries to prepare the health system and society when an outbreak of a disease occurs. From COVID-19, we learn that community participation in preventing COVID-19 is mandatory. This study aims to determine the relationship between sociodemographics, knowledge, and attitudes toward prevention measures for COVID-19. A cross-sectional study was conducted in the Mergangsan subdistrict, Yogyakarta City, Indonesia, in February-April 2022. A structured questionnaire was used to collect information from 350 participants. Univariate and bivariate analysis was performed to analyze the data. Our study found that age, gender, level of education, and attitude were significantly associated with COVID-19 prevention measures. Men-employed people and people with low knowledge and attitudes had a higher possibility of having poor prevention measures towards COVID-19. Considering the result of this study, increasing community participation in COVID-19 prevention measures requires interventions and programs tailored to specific layers by targeting men, working groups, and insufficient knowledge and behavior towards COVID-19.